The influence of supervision and competence of medical apparatus on the quality of medical services at Pringsewu Hospital, Lampung Province - Edi Sulaiman; Wirman Syafri; Dedeh Maryani; Faria Ruhana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The purpose of this study is to analyze the relationship and influence of employee performance supervision, and the level of employee competence on the quality of medical services provided by the Pringsewu Hospital organization. This research uses supervisory theory proposed by William H. Newman, competency theory by Walsh et al and service quality theory by Philip Kotler. The research method used is a quantitative approach with a descriptive type of research. The data analysis techniques used are descriptive  analysis techniques and Structural Equation Model  (SEM) analysis techniques. The results showed that statistical testing using the SEM-PLS method found that apparatus supervision had a significant effect on the quality of medical services with a positive relationship direction that showed that the better the apparatus supervision, the better the quality of medical services, and vice versa if the apparatus supervision is getting worse it will reduce the quality of medical services. Based on the calculation results show that the supervision of medical apparatus has an effect of 48.6% on the quality of medical services. For the results of statistical testing on the competence of medical apparatus that apparatus competence has a significant effect on the quality of medical services with a positive relationship direction that shows the higher the competence of the apparatus, it will improve the quality of medical services. Based on the calculation results, it shows that the competence of the medical apparatus has an effect of 22.3.